EFEKTIFITAS PEMBELAJARAN BIOLOGI DENGAN MODEL IQRA BERBASIS APLIKASI TEKHNOLOGI YANG DIKEMAS DALAM CD INTERAKTIF - Susi Winarni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2021)
This research is based on understanding natural phenomena to increase devotion to God Almighty. The purpose of this study is to help solve problems and foster greater motivation and curiosity towards the material on Biodiversity and to determine the effectiveness of learning biology. This study used a research design and R&D development. The research data obtained were analyzed by descriptive presentation. The results obtained; (1) the average student activity is 77.23%, process skills are 82.45% and learning outcomes are 70.23%; (2) the effect of student activity is R square value is 27.6%, and process skills are squared. 33.1%; (3) the average learning outcomes of the experimental class were 70.23% and the control group was 66.75%. These results show that the iqra model based on technology applications packaged in interactive CDs is effective for use in biology learning.